Spanish version of Jenkins Sleep Scale in physicians and nurses: psychometric properties from a Peruvian nationally representative sample - Villarreal-Zegarra, David (2022)
Objective: To evaluate the psychometric properties of the Spanish version of Jenkins Sleep Scale with 4 items (JSS-4) of the Peruvian health system's (PHS) nurses and physicians. Methods: We carried out a psychometric study based on secondary analysis in a sample from a nationally representative survey that used acomplex sampling design. The participants were physicians and nurses aged 18–65 years, working in PHS private and public facilities, who have fulfilled all JSS-4 items. We performed a confirmatory factor analysis. Reliability was evaluated via two estimates - classic alpha (α) and categorical omega (ω) coefficients. Also, we tested the invariance across groups of variables. The convergent validity was evaluated based on the relation between JSS-4 and PHQ-2 using Pearson's correlation coefficient and effect size (Cohen's d). Also, we designed normative values based on percentiles. Results: We included 2100 physicians and 2826 nurses in the analysis. We observed that the unidimensional model has adequate goodness-of-fit indices and values of α and ω coefficients. No measurement invariance was found between the groups of professionals and age groups; however, invariance was achieved between sex, monthly income, work-related illness, and chronic illness groups. Regarding the relation with other variables, the JSS-4 has a small correlation with PHQ-2. Also, profession and age-specific normative values were proposed. Conclusion: JSS-4 Spanish version has adequate psychometric properties in PHS nurses and physicians.